Gamified Digital Learning in Rural Indonesia: A Qualitative Case Study on Enhancing Engagement and Understanding in Elementary IPAS - Azudin Nur; Akhsanul In'am; Dyah Worowirastri Ekowati (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study addresses the digital divide affecting the implementation of the Merdeka Curriculum in rural Indonesian elementary schools, where limited infrastructure and teacher readiness constrain meaningful science learning. The study aimed to explore how gamified digital learning can enhance student engagement and conceptual understanding in IPAS classrooms. Employing a qualitative case study design, the research was conducted at State Elementary School 2 Sesaot in West Lombok, involving 1 IPAS teacher, 25 fifth-grade students, the school principal, and parents. Data were collected through classroom observations, semi-structured interviews, and document analysis, and analyzed using an interactive thematic model. The findings indicate that the integration of animated videos, visual slides, Wordwall, and Quizizz significantly improved learning outcomes, with 85% of students demonstrating better conceptual understanding of ecosystems, 78% reporting increased enjoyment, and 82% showing greater confidence in participation. The results suggest that digital media functioned as cognitive scaffolds, while gamification strengthened motivational engagement. Despite limitations related to short implementation duration and infrastructural constraints, the study highlights the feasibility of digital–gamified learning in low-resource settings. The study contributes theoretically by proposing a dual-pathway learning model and, practically, by offering policy-relevant insights to support sustainable, context-responsive digital learning in rural elementary schools. Keywords: digital learning, elementary education, gamification, motivation, science learning